Collective action when public good returns are heterogeneous - Abigail Barr; Trudy Owens; Ashira Perera (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2017)
We adopt a mixed methods approach to investigate whether and how heterogeneity in individual returns to a public good affects contributions. We engage smallholder farmers in Sri Lanka in: a one-shot, framed, lab-in-the-field experiment, within which the farmers' rates of return to the public good are exogenously varied; and a survey including a question about their willingness to contribute time to the construction of a specific, relevant to them public good. In the former, we find weak evidence that heterogeneity in individual returns increases contributions. In the latter we find that those facing higher returns contribute more. We conclude that heterogeneity in returns does not explain why collective action remains a challenge in farming communities in developing countries.
Keywords: C93; D81; O12; 330; lab-type behavioural experiment; collective action; heterogeneity; public goods